2015
DOI: 10.1038/nutd.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple binge alcohol on diet-induced liver injury in a mouse model of obesity

Abstract: Background:Alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) are highly prevalent liver diseases that may coexist and contribute significantly to liver disease-related mortality. Obesity is a common underlying risk factor for both disorders. There has been little research investigating the combined effects of high fat diet (HFD) and alcohol. Current mouse models of alcohol- or fat-rich diet alone do not lead to severe liver injury. There is a need to develop animal models recapitulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
(32 reference statements)
2
23
0
1
Order By: Relevance
“…The synergistic interactions observed in these epidemiological studies are well in line with mechanistic studies showing hepatotoxic effects from the combined exposure to alcohol and high‐fat diet above and beyond the sum of their individual effects (Duly et al, ; Minato et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The synergistic interactions observed in these epidemiological studies are well in line with mechanistic studies showing hepatotoxic effects from the combined exposure to alcohol and high‐fat diet above and beyond the sum of their individual effects (Duly et al, ; Minato et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…It could be speculated that a liver affected by steatosis may lack the capacity of a normal liver to recover after each episode of drinking during the break from alcohol intake. In support of this, animal studies show that intermittent alcohol administration serves as a “second hit” by aggravating hepatic oxidative stress and promoting steatohepatitis and fibrosis in mice with obesity‐induced steatosis (Duly et al, ; Minato et al, ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…MCP1, IP‐10, and KC have been shown to play a role in hepatic inflammation or injury (Mandrekar et al., ; Reiberger et al., ; Sermon et al., ). Our and other groups have shown that alcohol feeding induces MCP1, IP‐10, KC, Ly6G, and F4/80 (Duly et al., ; Sun et al., ; Zhong et al., ). However, the underlining mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 65%
“…Standard immunohistochemical analysis with citrate antigen retrieval was performed to localize 3‐nitrotyrosine (3‐NT) expression as previously described (Dixon et al , ). Standard immunofluorescence analysis was performed to localize F4/80, CD68 expression as previously described (Zhang et al , ; Duly et al , ). Haematoxylin–eosin‐stained paraffin‐embedded and Oil Red O stained frozen liver tissues isolated from mice were graded for hepatic steatosis and inflammation as described previously (Yamaguchi et al , ).…”
Section: Methodsmentioning
confidence: 99%